2015
DOI: 10.1111/pme.12896
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Event Rates Associated with Transforaminal and Interlaminar Epidural Steroid Injections: A Multi-Institutional Study

Abstract: Both transforaminal and ILESI are safely performed with low immediate and delayed adverse event rates when informed by evidence-based procedural guidelines. By demonstrating comparable safety, this study suggests that the choice between ILESI and TFESIs can be based on documented efficacy and effectiveness and not driven by safety concerns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 14 publications
3
55
0
2
Order By: Relevance
“…Even though the adverse event rates of both approaches were not evaluated in our studies because of a few complications reported and the short-term follow-up time, the choice between ILESI and TFESI should be based on documented efficacy and effectiveness but not driven by safety concerns [49]. Moreover, this meta-analysis was conducted on RCTs and observational studies respectively, and all of them were of high quality.…”
Section: Discussionmentioning
confidence: 98%
“…Even though the adverse event rates of both approaches were not evaluated in our studies because of a few complications reported and the short-term follow-up time, the choice between ILESI and TFESI should be based on documented efficacy and effectiveness but not driven by safety concerns [49]. Moreover, this meta-analysis was conducted on RCTs and observational studies respectively, and all of them were of high quality.…”
Section: Discussionmentioning
confidence: 98%
“…Facial warmth, redness, and flushing may occur 1-2 days after injection, lasting up to 3 days [29]. Psychiatric effects include sleep disturbance and mood change [29,30]. Patients with diabetes predictably experience an elevation in blood glucose levels.…”
Section: Minor Corticosteroid-related Adverse Effectsmentioning
confidence: 99%
“…Allergic reactions and infections are exceptional [30,35]. Epidural abscesses have been reported but are extremely rare, even in immunocompromised patients [30,[36][37][38].…”
Section: Severe Corticosteroid-related Adverse Effectsmentioning
confidence: 99%
“…However, serious complications of injections below conus-level appear to be rare [16, 17]. Complications of epidural corticosteroids against sciatica are usually limited to nausea, headache, dizziness, vasovagal attacks and flushing of the face [20, 21]. …”
Section: Introductionmentioning
confidence: 99%